Oxygen Vacancy-Enhanced Ni3N-CeO2/NF Nanoparticle Catalysts for Efficient and Stable Electrolytic Water Splitting - Xianghao Meng; Xin Zhao; Yulin Min; Qiaoxia Li; Qunjie Xu (Nanomaterials, 2024)
Highly efficient and cost-effective electrocatalysts are of critical significance in the domain of water electrolysis. In this study, a Ni3N-CeO2/NF heterostructure is synthesized through a facile hydrothermal technique followed by a subsequent nitridation process. This catalyst is endowed with an abundance of oxygen vacancies, thereby conferring a richer array of active sites. Therefore, the catalyst demonstrates a markedly low overpotential of 350 mV for the Oxygen Evolution Reaction (OER) at 50 mA cm−2 and a low overpotential of 42 mV for the Hydrogen Evolution Reaction (HER) at 10 mA cm−2. Serving as a dual-function electrode, this electrocatalyst is employed in overall water splitting in alkaline environments, demonstrating impressive efficiency at a cell voltage of 1.52 V of 10 mA cm−2. The in situ Raman spectroscopic analysis demonstrates that cerium dioxide (CeO2) facilitates the rapid reconfiguration of oxygen vacancy-enriched nickel oxyhydroxide (NiOOH), thereby enhancing the OER performance. This investigation elucidates the catalytic role of CeO2 in augmenting the OER efficiency of nickel nitride (Ni3N) for water electrolysis, offering valuable insights for the design of high-performance bifunctional catalysts tailored for water splitting applications.